(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2026)
Job satisfaction is a crucial psychological indicator that supports the effectiveness of employee performance, reflecting an individual’s ability to adapt and contribute to both personal and organizational goals. This study aims to examine the influence of self-esteem and self-efficacy on job satisfaction among employees at BKPSDM of Badung Regency. The entire population of 64 employees was surveyed using a census method. Data analysis was conducted through multiple linear regression using SPSS. The findings revealed that self-esteem has a positive and significant effect on job satisfaction, with a t-value of 3.059 exceeding the critical t-table value of 1.671. Similarly, self-efficacy showed a significant influence, with a t-value of 5.075. Simultaneously, both variables had a significant joint effect, with an F-value of 264.191, far above the F-table threshold of 3.15. These results underscore the importance of fostering self-confidence and improving work quality through institutional policies to enhance overall job satisfaction. Keywords: Self-esteem, Self-efficacy, Job Satisfaction.